System Identification of Heterogeneous Multirotor Unmanned Aerial Vehicle - Ayaz Ahmed Hoshu; Liuping Wang; Shahzeb Ansari; Abdul Sattar; Manzoor Hyder Alias Bilal (Drones, 2022)
An energy efficient heterogeneous multirotor unmanned aerial system (UAS) is presented in this paper, wherein, the aerodynamical characteristics of both helicopter and quadrotor are obtained in a single multirotor design. It features the energy efficiency and endurance of a helicopter, while keeping the mechanical simplicity, control and maneuverability of a quadrotor; employing a single large central rotor to get majority of the lift and four small arm canted rotors for control. Developing the stable and robust control strategy requires the accurate model of system. Due to the added mechanical complexities of the new design including the existence of couplings and gyroscopics, the modelling through the dynamic equations of the multirotor would not be possible in providing accurate results. Therefore, precise system modelling is required for the development of stable and robust control strategy. This paper proposes a novel system identification method with the objective to experimentally estimation of the precise dynamic model of the heterogeneous multirotor. The approach comprises of the utilization of input excitation signals, frequency sampling filter and derivation of transfer functions through complex curve fitting method. To validate the accuracy of the obtained transfer functions, the experimentally auto-tuned PID controllers are implemented over the transfer functions. Custom designed fight controller is used to experimentally implement the proposed idea. Presented results demonstrate the efficacy of the proposed approach for heterogeneous multirotor UAS.